The concept of the sexual reproduction cycle and its evolutionary significance - Bai, Shu-Nong (Frontiers in Plant Science, 2015)
The concept of a “sexual reproduction cycle (SRC)” was first proposed by Bai and Xu in 2013 to describe the integration of meiosis, sex differentiation and fertilization. This review discusses the evolutionary and scientific implications of considering these three events as part of a single process. Viewed in this way, the SRC is revealed to be a mechanism for efficiently increasing genetic variation, facilitating adaptation to environmental challenges. It also becomes clear that, in terms of cell proliferation, it is appropriate to contrast mitosis with the entire SRC, rather than with meiosis alone. Evolutionarily, it appears that the SRC was first established in unicellular eukaryotes and that all multicellular organisms evolved within that framework. This concept provides a new perspective into how sexual reproduction evolved, how generations should be defined and how developmental processes of various multicellular organisms should properly be compared.